Massive inguinoscrotal bladder hernia causing hydronephrosis: Two cases. (2015) - Aras, Bekir; Zeren, Sezgin; Ucar, Bercis Imge; Sanal, Bekir; Bayhan, Zulfu; Korkmaz, Mehmet; Sevim, Mehmet; Mestan, Metin; Yucel, Mehmet
Highlights: Complete bladder herniation are very rare compared to incomplete bladder herniation. Massive scrotal cystocele is usually defined with voiding symptoms. CT, ultrasonography and retrograde cystogram should be performed to determine the involvement of the bladder in cases of massive inguinoscrotal hernias. In massive scrotal hernia cases, bladder can protrude with the ureter causing hydronephrosis on the affected side. It is necessary to place urinary catheter to empty the urinary bladder to manage the pain and to decrease the risk of injury of bladder during the surgery.